Graphene removal by water-assisted focused electron-beam-induced etching – unveiling the dose and dwell time impact on the etch profile and topographical changes in SiO2 substrates - Szkudlarek, Aleksandra; Michalik, Jan M.; Serrano-Esparza, Inés; Nováček, Zdeněk; Novotná, Veronika; Ozga, Piotr; Kapusta, Czesław; De Teresa, José María (Beilstein Journal of Nanotechnology, 2024)
Graphene is one of the most extensively studied 2D materials, exhibiting extraordinary mechanical and electronic properties. Although many years have passed since its discovery, manipulating single graphene layers is still challenging using standard resist-based lithography techniques. Recently, it has been shown that it is possible to etch graphene directly in water-assisted processes using the so-called focused electron-beam-induced etching (FEBIE), with a spatial resolution of ten nanometers. Nanopatterning graphene with such a method in one single step and without using a physical mask or resist is a very appealing approach. During the process, on top of graphene nanopatterning, we have found significant morphological changes induced in the SiO2 substrate even at low electron dose values (<8 nC/μm2). We demonstrate that graphene etching and topographical changes in SiO2 substrates can be controlled via electron beam parameters such as dwell time and dose.
Keywords: direct writing; dwell time; electron dose; etching; graphene; maskless lithography; nanopatterning